Odpowiedzi

2010-03-29T19:20:40+02:00
2(2x-3)(x+1)-5(x-1)²=2(x-2)(x-1)
2(2x²+2x-3x-3)-5(x²-2x+1)= 2( x²-x-2x+2)
4x²+4x-6x-6-5x²+10x-5=2x²-2x-4x+4
4x²+4x-6x-6-5x²+10x-5-2x²+2x+4x-4=0
-3x²+14x-15=0
Δ=b²-4ac
Δ=196-180
Δ=16
√Δ=4

x1= -b-√Δ / 2a
x1=-14-4 / 3*(-3)
x1=-18 / (-6)
x1=3

x2= -b+√Δ / 2a
x2=-14+4 / (-6)
x2=-10 / (-6)
x2= 5/3






-4x²-16x+9=0
a=-4
b=-16
c=9
Δ=b²-4ac
Δ=256+144
Δ=400
√Δ=20

x1= -b-√Δ / 2a
x1=16-20 / (-8)
x1=(-4) / (-8)
x1=1/2

x2= -b+√Δ / 2a
x2=-16+20 / (-8)
x2=4 / (-8)
x2= -1/2